M.G Analisis Salam pada transaksi Jual Beli Gabah - Gustan, Mutmainnah (IAIN Parepare, 2024)
This study aims to analyze the application of the Salam contract in rice trading. The research method used is qualitative with a case study approach. Data were collected through interviews and documentation. The results show that the Salam contract can increase farmers' capital and guarantee the sale of rice at a predetermined price. However, challenges include ensuring the quality of the rice and timely delivery. Conclusions highlight the importance of implementing proper monitoring and contractual terms to mitigate risks.